Square Toiletries Ltd: Developing a marketing Strategy and Reaching to Potential Customers of Sepnil - Islam, Farhan (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.